PERANCANGAN TATA LETAK BAHAN BAKU DENGAN METODE GRAVITY LOCATION MODEL (GLM) DI PT PERTANI (PERSERO) CABANG D.I. YOGYAKARTA - Agustinus Andrie Prasetyo; Widya Setiafindari; Alex Alfandianto (Jurnal DISPROTEK, 2018)
PT Pertani (Persero) UPB Sleman is a company engaged in the processing of seeds, especially seeds of rice plants. In this factory, seeds are divided into KS (Dry Rice Field), KK (Dry Dry) and KB (Dry Clean). The seeds are stored in a warehouse with a warehouse with size 30 meters X 18 meters and a capacity of 200 tons. And the distance of KK to production room is 15-20 meter, the distance of KS to production room is 4 meter, The arrangement of KB 2-2,5 meter with condition of layout less well arranged that it became obstacles for workers on path to production room. The method of research used Gravity Location Model (GLM). It is a branch of Supply Chain Management for facility location. This research aims to analyze the layout from each sector in PT Pertani (Persero) warehouse. The conclusion of this research is using the method with size and capacity to measure the farthest and the nearest used as consideration to design layout in the warehouse.